Microsoft Windows 2000 - Kemper, Mary. (Cambridge, MA : Course Technology, 2000)
This book is divided into three parts: Getting started with Windows 2000; Working with Programs, Files, and Folders; and Formatting a Disk.
Keywords: Microsoft Windows; Microsoft Windows (Computer file)